IMPERIAL DISTRICTS AS FEDERAL AND REGIONAL ELEMENTS OF THE HOLY ROMAN EMPIRE 1500–1806 - Wüst, Wolfgang (Advances in Social Sciences Research Journal, 2020)
The creation of the Imperial Circles (= Reichskreise) was an overdue answer to the powerlessness of the Empire and the Estates in matters of the preservation of peace in the countryside, the organization of the Supreme Court, the control of taxes, begging, the poor, customs and coin matters, the conscription of the Imperial Army, health care – formed by the medical Policey with regard to the supply of drinking water, protection against epidemics and plague – and many other points in the early modern process of civilization. These included, for example, the construction of cross-border roads and streets and the settlement of territorial prestige and border disputes. Some of these were certainly more of a requirement than an everyday practice. Since the 16th century, most of the administrative work was then carried out by the increasing competence of county councils. In combination with their territorial system of offices and government, they had new instruments of regional planning control at their disposal. For urgent tasks such as regional and supra-regional road construction, the fight against epidemics and crime, and customs, coinage or trade policy, the county councils (= Kreiskonvente) were often too “small”, especially in the territorial area of southern Germany, but the Reich as a whole was far too “large”" to find and implement practicable solutions. Up to now it was a research desideratum to classify the imperial circles into the European system of federal structures. My contribution aims to close this gap.